Effects of Periodized vs. Nonperiodized Resistance Training on Army-Specific Fitness and Skills Performance. Issue 3 (March 2020) - Heilbronn, Brian E.; Doma, Kenji; Gormann, Dale; Schumann, Moritz; Sinclair, Wade H.
Abstract : Abstract: Heilbronn, BE, Doma, K, Gormann, D, Schumann, M, and Sinclair, WH. Effects of periodized vs. nonperiodized resistance training on army-specific fitness and skills performance. J Strength Cond Res 34(3): 738–753, 2020—This study investigated the effects of periodized resistance training (PRD) and nonperiodized resistance training (NPRD) on army-specific fitness and skills performance measures. Forty-nine serving members of the Australian Army were randomly assigned to 1 of 3 training groups: PRD, NPRD, or no-resistance training (NRT). Resistance training (RT) was performed during PRD and NPRD twice a week for 9 weeks, over a 15-week period, as part of a structured strength and conditioning program. Baseline, mid- and post-testing measures included anthropometric, strength, and army-specific outcome measures. Results indicated that participants who undertook RT significantly improved in 3 repetition maximum (3RM) squat, deadlift, and floor press for both RT groups, at mid- and post-testing ( p < 0.05), when compared with NRT. Significant improvements were also observed in 5-km weight load marching postintervention similarly for PRD ( p < 0.05) and NPRD ( p < 0.01) and simulated fire and movement for both RT groups at both time points ( p < 0.01), compared with the NRT group ( p > 0.05). Although little difference was observed between periodization models, the current findings suggest greater advantage in developing army-specific performances if a structured RT protocol is included in a generic physical training program compared with a NRT protocol. Therefore, a structured RT program should be considered for military personnel aiming to optimize army-specific fitness and skills performance.